ANALYSIS OF POTENTIAL DEVELOPMENT OF AGRO-EDU TOURISM BASED ON COMMUNITY EMPOWERMENT IN THE CIPANAS DAM AREA - Dwi Wahyu Wamenarno; Mohammad Syaom Barliana; Asep Yudi Permana (Journal of Development and Integrated Engineering, 2022)
One of the sectors that are progressing and are growing rapidly, especially in Indonesia today is tourism. Tourism has an important role in increasing the income of a region. In terms of employment, the tourism sector can also be a solution to reduce the unemployment problem which is currently rife in various parts of the country. In terms of cultural diversity and natural beauty, Indonesia can be one of the unique tourist destinations in this regard. This study aims to analyze the potential for developing agro-Edu tourism based on community empowerment in the Cipanas Dam area so that it has a positive impact on the economy, especially the economy of the local community. The research method used in this study is descriptive with a qualitative approach, where the descriptive qualitative method is a research method based on the philosophy of postpositivism used to examine the condition of natural objects (as opposed to experiments) where the researcher is the key instrument of data collection techniques carried out manually triangulation (combined), data analysis is inductive/qualitative, and qualitative research results emphasize meaning rather than generalization. The results of the research from the potential of Agro-Edu Tourism in the Cipanas dam area can be developed in several location spots, including by utilizing the edge of the dam as a pedestrian tracking path along the green belt in the form of trees; the development of a camping ground that can accommodate tourists to spend the night while still being able to enjoy the atmosphere of the outdoors on the edge of the lake; mango fruit agro-tourism area; The Tower of View in the Rest Area and the planned Cipanas Terrace area downstream of the dam.